2016
DOI: 10.3390/w8080317
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Alteration Associated with Dam Construction in a Medium-Sized Coastal Watershed of Southeast China

Abstract: Sustainable water resource management requires dams operations that provide environmental flow to support the downstream riverine ecosystem. However, relatively little is known about the hydrologic impact of small and medium dams in the smaller basin in China. Flow duration curve, indicators of hydrologic alteration andrange of variability approach were coupled in this study to evaluate the pre-and post-impact hydrologic regimes associated with dam construction using 44 years of hydrologic data in the Jiulong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 71 publications
(137 reference statements)
2
12
1
Order By: Relevance
“…Therefore, the operation of NEJ dam reduced the frequency and magnitude of high flow and diminished extreme discharge in the downstream basin. The results are consistent with those reported in previous studies [54,55].…”
Section: Hydrological Alterations Caused By Dam Constructionsupporting
confidence: 94%
“…Therefore, the operation of NEJ dam reduced the frequency and magnitude of high flow and diminished extreme discharge in the downstream basin. The results are consistent with those reported in previous studies [54,55].…”
Section: Hydrological Alterations Caused By Dam Constructionsupporting
confidence: 94%
“…As in other studies, the frequency and duration of high and low pulses (group 4 parameters) and the rate and frequency of hydrologic changes (group 5) were often the most affected elements of the hydrologic regime. For example, Zhang et al (2016) reported greater variations for the IHA parameters of groups 4 and 5, especially for the number and duration of low pulses, in studies in southwest China. Richter et al (1996) also observed the greatest alteration to elements of the frequency and duration elements of the flow regime captured by IHA groups 4 and 5.…”
Section: Hydrological Alterations In Dammed and Undammed Riversmentioning
confidence: 96%
“…To assess hydrologic alterations in aquatic ecosystems, Richter et al (1996) proposed a method for evaluating 33 different indicators of the flow regime, called Indicators of Hydrologic Alteration (IHA). This method has been widely used all over the world (Richter et al, 1996(Richter et al, , 1997Magilligan and Nislow, 2005;Rocha, 2010;Li and Qiu, 2016;Zhang et al, 2016;Sabino, 2017;Timpe and Kaplan, 2017). The type and magnitude of dam-induced hydrologic change found across these studies vary greatly as a function of climate, geography, dam type, and reservoir operation protocols, suggesting that regional analyses are needed to characterize relevant aspects of flow alteration in specific areas.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the needs of economic and social development, many hydropower stations have been built in Southwest China. Meanwhile, the construction of hydropower stations is often accompanied by the appearance of large reservoirs and dams [1,2]. Humans have had a habit of living near rivers since ancient times, which has resulted in large population settlements in the downstream areas of the reservoir [3].…”
Section: Introductionmentioning
confidence: 99%